ANSWERS: 1
  • Did you mean 'recurrence relations'? Suppose the sequence is defined by k[n] = P*k[n-1] + Q*k[n-2] Take four values and get two simultaneous equations: k3 = P*k2 + Q*k1 k4 = P*k3 + Q*k2 So: P = (k4 k1 - k3 k2)/(k3 k1 - k2^2) Q = (k3^2 - k4 k2)/(k3 k1 - k2^2) So in the first answer: 0,20,36,48.8 P = (48.8 * 0 - 36*20) /(36*0 - 20^2) = 1.8 Q = (36^2 - 48.8*20) / (36*0 -20^2) = -0.8 Sure nuff, 36 = 1.8*20 -0.8*0 48.8 = 1.8*36 -0.8*20 So the sequence is k[1] = 0, k[1] = 20, k[n] = 1.8*k[n-1] - 0.8*k[n-2]

Copyright 2018, Wired Ivy, LLC

Answerbag | Terms of Service | Privacy Policy